Effect of irreversibility on COP of double effect steam absorption chillers - Abd Majid, M.A. (Asian Research Publishing Network, 2016)
Major irreversibility's in the absorption chillers are due to heat transfer between the absorption cycles and the environment. This effect also occurs for LiBr/H2O steam absorption chillers. This study investigated the effect of external heat transfer processes on LiBr/H2O steam absorption chillers installed at two district cooling plants in Malaysia. The study was done by evaluation of operating data. The heat transfer processes occurring at the desorbers, evaporators, condensers and absorbers for the absorption chillers at these two plants were investigated using reversible and zero order models. It is noted that the trends shown by the reversible and zero order models indicate the irreversibility occurred for the absorption chillers at both plants. The COPs figures for reversible and zero order models for the absorption chillers at one of the plant indicate lower values. One possible cause of this occurrence was due to lower temperatures of returned chilled water. Hence in order to improve COP, the temperatures of returned chilled water should be increased. Â© 2006-2016 Asian Research Publishing Network (ARPN).